2021
DOI: 10.1136/bmjopen-2020-046464
|View full text |Cite
|
Sign up to set email alerts
|

Determining the burden of missed opportunities for vaccination among children admitted in healthcare facilities in India: a cross-sectional study

Abstract: ObjectivesChildren accessing healthcare systems represent a vulnerable population with risk factors for poor health outcomes, including vaccine-preventable diseases. We aimed to quantify missed vaccination opportunities among hospitalised children in India, and identify vaccination barriers perceived by caregivers and healthcare providers.DesignCross-sectional study.SettingTwo public-sector tertiary-care hospitals in northern India, during November 2018 and March 2019.ParticipantsWe tracked 263 hospitalised ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Our data draw attention to the high proportion of children missing an opportunity to get vaccinated at hospital level. A similar proportion has been found in a recent study performed in northern Indian hospitals 24. This could be explained by vaccine shortage at hospital level but also by the belief in the false contraindication for vaccination in a sick child among caregivers and healthcare workers.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our data draw attention to the high proportion of children missing an opportunity to get vaccinated at hospital level. A similar proportion has been found in a recent study performed in northern Indian hospitals 24. This could be explained by vaccine shortage at hospital level but also by the belief in the false contraindication for vaccination in a sick child among caregivers and healthcare workers.…”
Section: Discussionsupporting
confidence: 85%
“…A similar proportion has been found in a recent study performed in northern Indian hospitals. 24 This Open access could be explained by vaccine shortage at hospital level but also by the belief in the false contraindication for vaccination in a sick child among caregivers and healthcare workers. For example, a study in Haiti reported that up to 13% of reasons for undervaccination were child illness, despite the fact that mild infections should not prevent vaccination.…”
Section: Characteristics Of Children With Movmentioning
confidence: 99%
“…Compared to other regional countries UNICEF statistics report in 2015 shows the following results: Saudi Arabia (96%), Turkey (97.6%), Jordan and Iran (98%) and Syria (58%) [16] . Several reports from other countries revealed higher rates of MOI in comparison to our results; as that reported in Africa (47%) [22] , Ethiopia (49.1%) [23] , India (65.4%) [24] , and in Kenya (75%) [25] ; conversely, it was higher than that reported in China (12.6%) [26] , and South Africa (14.1%) [27] , and relatively similar to that reported in Sudan (35%) [28] and Pakistan (31.78%) [29] . These disparities in the MOI prevalence among the studies could be due to differences in MOI assessment methodologies regarding the study design, the study settings, the study population, study period differences, sample size, sampling techniques and low accessibility for healthcare facility infrastructure.…”
Section: Discussionsupporting
confidence: 60%
“…Out of 43 children offered vaccination, there was 65% uptake. In another study, 65.4% (172/263) of hospitalised children were under‐vaccinated on presentation to hospital to two tertiary paediatric hospitals in India 11 . A study of 2329 children aged between 0 and 2 years found immunisations were delayed greater than or equal to 2 months in 18% (355) of children 12 .…”
Section: Discussionmentioning
confidence: 98%
“…In another study, 65.4% (172/263) of hospitalised children were under-vaccinated on presentation to hospital to two tertiary paediatric hospitals in India. 11 A study of 2329 children aged between 0 and 2 years found immunisations were delayed greater than or equal to 2 months in 18% (355) of children. 12 Successful administration of rotavirus vaccine has also been shown in neonatal intensive care units.…”
Section: Discussionmentioning
confidence: 99%